Modelagem fuzzy aplicada a políticas públicas: proposta de um indice municipal de qualidade ambiental - Silva, Fábio Nowak da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to develop an environmental quality index for the city of Votorantim (SP), fuzzy applied to support the decisions of the Municipal Council for the Environment (COMDEMA). By building a previously structured information collection system, it creates a mathematical model using the theory of fuzzy sets, noting the economic reality, social, administrative and environmental municipality. Three groups of indicators were selected in order to seek an equation that expresses in the best way possible the reality of the city with respect to its environmental quality together later in a global index. The calculation was performed according to concepts of mathematics fuzzy, with the help of Fuzzy Logical Toolbox 2.1 program package Matlab 6.1 (The MathWorks, Inc.), which provides functions for files and some applications of the theory of fuzzy sets. The work created a method of inference about human action in cities in relation to the environment, often relegated to the background in public policy discussions. The development of this index and its application to the municipality of Votiorantim, served as an important social mobilization tool serving the best rates for your comparison between the first inference, in 2000, and the second, in 2013, there was local development .so measure enabling the development of several locations

O objetivo desse trabalho foi construir um índice de qualidade ambiental para o município de Votorantim (SP), fuzzy aplicado ao suporte às decisões do Conselho Municipal de Meio Ambiente (COMDEMA). Através da construção de um sistema de coleta de informações previamente estruturado, cria-se um modelo matemático, utilizando a teoria dos conjuntos fuzzy, observando a realidade econômica, social, administrativa e ambiental do município. Foram selecionados três grupos de indicadores como forma de buscar uma equação que expresse da melhor forma possível a realidade do município com relação à sua qualidade ambiental unidos, posteriormente, em um índice global. O cálculo foi realizado segundo conceitos da matemática fuzzy, com auxílio do pacote Fuzzy Logical Toolbox 2.1 do programa Matlab® 6.1 (The MathWorks, Inc.), que disponibiliza arquivos e funções destinados a algumas aplicações da teoria de conjuntos fuzzy. O trabalho criou um método de inferência sobre a ação antrópica nas cidades em relação ao meio ambiente,muitas vezes relegado a segundo plano nas discussões de políticas públicas. A elaboração deste índice e sua aplicação ao municipio de Votiorantim, serviu como uma importante ferramenta de mobilização social em prol de índices melhores pois sua comparação entre a primeira inferencia,no ano de 2000, e a segunda, no ano de 2013, houve evolução local.Portanto possibilitando mensurar o desenvolvimento da localidades diversas
Keywords: Politicas publicas; Indicadores ambientais; Qualidade ambiental; Conjuntos difusos; Environmental indicators